Research on Construction of High-Quality Application-Oriented Talent Cultivation System for Internet of Things Engineering: Based on Educational Psychology - Nie, Yalin; Wang, Haijun; Liu, Baoluo; Yang, Shangsen (Frontiers in Psychology, 2022)
High-quality talent cultivating of Internet of Things engineering is the basis for the rapid development of Internet of Things technology. In order to train high-quality application-oriented Internet of Things technical talents, guided by educational psychology, this paper conducts in-depth research and analyzes the characteristics of Internet of Things engineering, makes professional talent cultivating programs and cyclical adjustment plans, builds a high-quality teaching system based on the professional knowledge system of the Internet of Things, explores the "spiritual level" and "psychological level" characteristics of teachers and students in teaching, highly integrates "Industry-University-Research-Competition" from the perspective of students, teachers and colleges, infiltrates positive psychological cues appropriately, formulates the construction method of the "student teaching assistant" auxiliary system to enhance the efforts to promote learning by learning, and finally innovates the talent cultivating system for Internet of Things engineering. The implementation results show that the students trained by this system have a solid foundation of knowledge related to Internet of Things engineering and strong engineering practice application, adaptability and innovation ability.